Practical teacher’s perception towards code switching in the English language classroom / Mohd Hasren Yusuf - Yusuf, Mohd Hasren (2011)
This study sets out to learn more about the perception of practical teachers towards Code Switching in the English language classrooms. The study investigated 55 practical teachers from Universiti Teknologi MARA Melaka, who are TESL students doing their three months practicum in schools in Melaka. They experienced teaching different levels of students’ proficiency and this led them to code switch. A set of questionnaire containing 20 items using the 5-points Likert-type scale was administered to measure the presence of codeswitching in classrooms, the affective support and the learning success. The study proposed two hypotheses which were tested using Pearson product moment correlation analyses. The study found that practical teachers perceived code-switching as a positive strategy due to the various functions it has. There are significant relationships between teachers’ code-switching and learners’ affective support and teachers’ code-switching and learners’ learning success. Teachers also showed a favourable support for future code-switching in the English classrooms. It is strongly believed that code-switching is an effective teaching strategy when dealing with low English proficient learners